DEMOGRAPHIC STUDY AND THE MANAGEMENT OF URETHRAL STRICTURE IN H. ADAM MALIK GENERAL HOSPITAL - Utomo, Doli Catur; Prapiska, Fauriski Febrian; Nasution, Ramlan (Indonesian Urological Association, 2022)
Objective: This study aims to describe the demographic data and clinical characteristics of patient with urethral stricture in Adam Malik Hospital. Material & Methods: This research was a retrospectively designed descriptive study, with a consecutive sampling method. Data such as age, clinical symptoms, length and locations of stricture, and the type of operation conducted, were obtained from medical records from May 2013 to June 2017. All subjects had given consent that their medical records can be involved in this research. Results: 60 urethral stricture cases were found, with trauma as a major cause with a percentage of 58.3% of the cases. While the iatrogenic cause (combining post cystoscopy and post operation) contributed only 15% of the total cases. The mean age for subjects was 34.07 ± 2.044 and most of them complained about urinary retention and difficulty in initiating micturition (hesitancy). In contrast, the symptoms that were rarely revealed by subjects were weak stream and pain during micturition, with total of only 3.4% of the cases. A large part of the urethral stricture cases originated from the Bulbous part (30%) with the stricture mean length is 18.32 ± 1.944, and the part where stricture would least likely happen is the membranous and the prostatic part (8.3%). Urethrotomy (Sachse) was the favorite surgical technique used by urologists to manage urethral strictures. Conclusion: This research showed that the characteristics of patients who were diagnosed having urethral stricture in Indonesia are similar with the results from other studies conducted before. It also showed even though urethroplasty has vast advantages compared to the conventional urethrotomy (Sachse), it was still underappreciated by the surgeons.